Irrigation Development Planning: Aspects of Pakistan Experience by I. D. Carruthers. Department of Economics, Wye College (University of London), Ashford, Kent, December 1968. (The Pakistan Development Review, 1970)
In this little book, the second in a series of Agrarian Development Studies, issued by the Economics Department of Wye College, the author draws upon four years' experience with the consultants to the Water and Power Development Authority in West Pakistan to review the main technical and economic factors to be considered in planning irrigation development. The first chapter describes, in general terms, some of the basic relation¬ships between crop growth and water and drainage conditions. The author warns that in arid areas water tends to be regarded as a unique resource. Assigning supreme priorities to single resources can be very damaging to economic development since mere technical feasibility is regarded as justifying irrigation projects, regardless of whether they are economically justified.